The size and structure of China's full-covered fiscal expenditure - Wang Dehua (China Finance and Economic Review, 2015)
Background: Many Chinese literatures compared the size and structure of fiscal expenditure between China and the developed countries. However, due to the statistic differentiation, this kind of comparison may not be accurate. Methods: Referring to the standard of the International Monetary Fund (IMF) (2001), I measured the size from 2003 to 2012 and the structure in 2012 of China's full-covered fiscal expenditure. Furthermore, I compared the size of China's fiscal expenditure with OECD countries. Results: I find - as China is going through the "dual-peak" period, the peak of infrastructure development and social welfare expansion the overall fiscal expenditure share of GDP has risen from around 31% in 2003 to around 37% in 2012. Conclusions: The ratio of infrastructure expenditure to the whole fiscal expenditure is about 39%, while spending on social welfare is only about 41%.
Keywords: 330; Fiscal expenditure; Full-covered; Dual-peak